Intentionally holistic knowledge intensive service systems. (19th September 2011) - Wilby, Jennifer; Macaulay, Linda; Theodoulidis, Babis
This paper applies a new framework of systems science to service science. This new framework reveals the effect of the interactions between systems principles and system structure in revealing complex systems behaviour, demonstrates why such methodologies are classed as being systemic, and how these systemic methodologies can be used to explore, design and manage emergent complex behaviour in practice. This paper then proposes that this framework of ideas can be transferred to inform the content of the existing roadmap for researching service systems, and thereby improve the design of new intentionally holistic service systems and the understanding and management of existing service systems and knowledge intensive service systems. Further research will investigate cases of complex scenarios in service systems, with the aim of transferring that knowledge (and its implications) to the fields of research, practice and education in both systems science and service (systems) science.